Effects of Light Intensity on in Vitro Regeneration Of Stevia Rebaudiana Bertoni, Bacopa Monnieri L. And Solanum Tuberosum L. - Banu, Tanjina Akhtar; Akter, Shamima; Akter, Shahina; Goswami, Barna; Mollika, Sanjida Rahman; Momtaz, Nasima; Habib, Md Ahashan; Amin , GM Al; Khan , Md Salim (Bangladesh Journal of Botany, 2023)
Light is the most essential factor controlling plant growth, morphogenesis, metabolism and chlorophyll content of plant cells, tissues and organ culture. The present investigations were carried out to find out effects of different light intensities (210, 500, 1000, 1500, 2000, 2500 and 3000 lx) on the regeneration of three plants, namely Stevia rebaudiana Bertoni., Solanum tuberosum L. and Bacopa monnieri L. Results showed that light intensity has a direct effect on plant growth in vitro. There was less time for shoot initiation and the highest mean number of shoots/explants (9.75 ± 3.862) of S. rebaudiana was observed from the nodal explants when the culture was maintained at 1000 lx light conditions. At maximum light intensity (3000 lx) best result was recorded for S. tuberosum. A distinct intensity of light, 1500 lx showed the best outcome both for the number and length of shoots of B. monnieri (p = 0.00). The present study also demonstrated the relationship between root growth and light condition. Bangladesh J. Bot. 52(1): 53-60, 2023 (March)